Fundamentals of Sustainable Dwellings - Friedman, Avi.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics, 2012)
Despite a prolonged slump in the housing market, the demand for residential green building remains strong. More than ever, professionals need reliable information about how to construct or retrofit livable, sustainable, and economical homes. With Fundamentals of Sustainable Dwellings, Avi Friedman provides that resource. While other books on residential green building are often either superficial or overly technical, Friedman gets it just right, delivering an illustrated, accessible guide for architects, developers, home builders, codes officials, and students of architecture and green design. Friedman charts a new course for residential building$1 (Bone in which social, cultural, economic, and environmental values are part of every design decision. The book begins with a concise overview of green building principles, covering topics such as sustainable resources and common certification methods. Each following chapter examines a critical aspect of green home construction, from siting to waste management options. Friedman provides basics about energy-efficient windows and heating and cooling systems. And he offers innovative solutions like edible landscaping and green roofs. Friedman knows that in green building, ideas are only as good as their execution. So in each chapter valuable data is assembled and a contemporary project in which designers strove to achieve sustainability while adhering to real-world constraints is featured. The result is a practical guide for every professional in the burgeoning field of residential green building.s
Preface -- Acknowledgements -- Chapter 1. Principles of Sustainable Dwellings -- Chapter 2. Siting a Home -- Chapter 3. Sustainable Residential Design Concepts -- Chapter 4. Unit-Planning Principles -- Chapter 5. Constructing a Home -- Chapter 6. Building Materials -- Chapter 7. Energy-Efficient Windows -- Chapter 8. Heating and Cooling Systems -- Chapter 9. Healthy Indoor Environments -- Chapter 10. Water Efficiency -- Chapter 11. Green Roofs -- Chapter 12. Edible Landscaping and Xeriscaping -- Chapter 13. Waste Management and Disposal -- Bibliography -- Illustration Credits -- Case Study Projects Team -- Case Study Projects Photographers -- Index.
Keywords: Environmental sciences; Architecture; Urban Ecology; Waste disposal; Sustainable development; Environment; Sustainable Development; Urbanism; Building Types and Functions; Waste Management/Waste Technology; Urban Ecology